Anaemia and severe malarial anaemia burden in febrile Gabonese children: a nine-year health facility based survey - Marielle Karine Bouyou-Akotet; Denise Patricia Mawili Mboumba; Eric Kendjo; Fanckie Mbadinga; Nestor Obiang-Bekale; Pacome Mouidi; Maryvonne Kombila (Journal of Infection in Developing Countries)
Introduction: Anaemia remains a major cause of poor health in children and pregnant women living in sub-Saharan Africa. Malaria is one of the main causes of anaemia in endemic countries. At the time of decreasing Plasmodium falciparum infection prevalence among children, it was essential to analyze the evolution of anaemia and severe malarial anaemia (SMA), the most frequent clinical manifestation of severe malaria, in Gabon. Methodology: Yearly recorded haemoglobin levels of febrile children aged below11 years, who benefitted from microscopic malaria diagnosis, were retrospectively analyzed to determine the evolution of anaemia and SMA prevalence throughout a nine-year period between 2000 and 2008. Results: Anaemia prevalence remained high both in P. falciparum-infected children (between 87.6% and 90.7%) and in uninfected children (between 73.5% and 82.6%). Although the risk of developing severe anaemia ranged between 1.9 [0.9-3.8] in 2000 and 3.0 [1.3-6.5] in 2007, SMA prevalence did not significantly change during the study period, varying from 6.0% to 8.0%. From 2001, the frequency of SMA was comparable between children younger than five years of age and children older than five years of age. Conclusions: The decreasing malaria prevalence previously observed in Gabon between 2000 and 2008 was not associated with a significant reduction of anaemia and SMA burden among children. Furthermore, other factors such as nutritional deficiencies, which may not be negligible, must be investigated in this vulnerable population